Nitidine and Paclitaxel-Coloaded Lipid-Chitosan Hybrid Nanoparticles Overcoming ABCB1-Mediated Multidrug Resistance in Ovarian Cancer - Ozturk, Rabia Yilmaz; Durasi, Elif; Calik, Hilal; Ari Yuka, Selcen; Cakir, Rabia (WILEY-V C H VERLAG GMBH, 2025)
Multiple drug resistance, which leads to tumor recurrence and contributes to high mortality rates in ovarian cancer, must be overcome for successful treatment. Within this study, the efficacy of lipid-chitosan hybrid nanoparticles (LPHNPs) with NTD as an ABCB1 inhibitor and PTX as a chemotherapeutic agent in ABCB1 overexpressed ovarian cancer cells are explored. Sensitive ovarian cancer cells acquire resistance by continuous paclitaxel treatment and confirm by the resistance index and ABCB1 expression by quantitative reverse transcription polymerase chain reaction. PTX-NTD-loaded LPHNPs (N-PTX-LPHNPs) are synthesized via ionic gelation and characterized by the dynamic light scattering method, in vitro release, encapsulation, and loading efficiency, FTIR, and scanning electron microscopy. XTT, Rho-123 accumulation assay, and DCFH-DA staining are conducted to examine the drug resistance inhibition and anticancer activity of NTD and N-PTX-LPHNPs. Bioinformatics analyses are performed to evaluate the absorption, distribution, metabolism and excretion, toxicity properties of NTD and the interaction between the PTX-NTD combination and ABCB1. NTD shows high binding affinity to ABCB1 and cytotoxicity against ovarian cancer cells. Moreover, the PTX-NTD combination-loaded nanoparticles increase PTX accumulation and intracellular ROS levels, enhance anticancer activity, and overcome resistance to ovarian cancer. The results highlight the NTD-PTX-loaded LPHNPs as a potential therapeutic for ABCB1 overexpressed ovarian cancer.
Keywords: ABCB1; bioinformatics; cancers; lipid-chitosan hybrid nanoparticles; multidrug resistances; DRUG-DRUG INTERACTION; CO-DELIVERY; CELLS; CYTOTOXICITY; MECHANISMS; CARCINOMA; THERAPY; EXTRACT; ENHANCE; Pharmacology & Pharmacy